USING BREATHING AND MEDITATIVE TECHNIQUES TO DEAL WITH UNCERTAINTY AND ANXIETY: A PERSONAL EXPERIENCE - SHYAM, GEETA (Society Register, 2020)
The scale of disruption caused by the COVID-19 pandemic is expected to adversely affect the mental health of a large number of people. In this Note, the author shares her strategies for dealing with uncertainty and anxiety. Recounting her personal experiences, she reveals how simple breathing exercises and meditation practices helped her accept and respond to a traumatic experience as well as an unexpected illness. A number of studies appear to support the view that breathing exercises and meditation can help people manage anxiety. It is suggested that these studies highlight the relevance and value of these practices in the current distressing conditions.